Analysis Of Influence Factors Msme Taxpayer Compliance With Implementation Of Tax Obligations - Chudri, Intan Rizkia; Purnamasari, Desy; Umar, Zulkifli; Syavira, Dinar (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2023)
The purpose of this research is to determine factors that affect taxpayer compliance on micro, small, and medium enterprises (UMKMs) in the city of Sabang. The factors consist of taxation, awareness of taxpayers, modern tax administration systems, and tax examination. The method used is a quantitative research design. The data used in this study are primary data. Primary data were obtained through the distribution of questionnaires to owners of UMKMs in the city of Sabang who are registered with the Aceh Besar Primary Tax Office and operate within the Aceh Besar District, Aceh Pidie District, and Sabang City. The sample in this study consists of 90 randomly selected respondents using random sampling technique. The data analysis technique used is multiple linear regression analysis. The data testing conducted in this study includes instrument testing (validity test and reliability test) and classical assumption testing (normality test, multicollinearity test, and heteroskedasticity test). For hypothesis testing, the researcher used the F-test and t-test. The results of this study partially indicate that each variable such as taxation knowledge, taxpayer awareness, modern tax administration system, and tax examination have a significant influence on taxpayer compliance. Meanwhile, the simultaneous testing results show that all variables have a significant influence on taxpayer compliance